1985
DOI: 10.1002/ppul.1950010406
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilators and diuretics in children with bronchopulmonary dysplasia

Abstract: Pulmonary function tests (PFT) were obtained during the course of a self-controlled study of six children aged 5 to 43 months who had moderate to severe bronchopulmonary dysplasia (BPD). Changes after the administration of intravenous (IV) furosemide (2 mg/kg), inhaled isoproterenol (0.2 cc, 1:200), inhaled atropine sulfate (0.05 mg/kg), and a placebo were assessed. The study indicated the furosemide and atropine significantly (P less than 0.05) increased dynamic compliance (CL) for the group. A decrease in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Three studies examined the effects of a combination of spironolactone and chlorothiazide, 8,19,22 2 studies examined the effects of a combination of spironolactone and hydrochlorothiazide 7,27 and 8 examined the effects of furosemide (Table 1). 5,9,21,[23][24][25][26][27] Every trial measured dynamic pulmonary compliance and pulmonary resistance and these measures were used as comparative tools in this review.…”
Section: Description Of the Resultsmentioning
confidence: 99%
“…Three studies examined the effects of a combination of spironolactone and chlorothiazide, 8,19,22 2 studies examined the effects of a combination of spironolactone and hydrochlorothiazide 7,27 and 8 examined the effects of furosemide (Table 1). 5,9,21,[23][24][25][26][27] Every trial measured dynamic pulmonary compliance and pulmonary resistance and these measures were used as comparative tools in this review.…”
Section: Description Of the Resultsmentioning
confidence: 99%
“…Logvino et al [12] measured pulmonary resistance in six BPD patients 4±43 months old and found no signi®cant change after administration of isoproterenol. Kao et al [10,11] reported two studies.…”
Section: Discussionmentioning
confidence: 98%
“…The use of salbutamol was shown to be effective in improving compliance and resistance in very low birth weight (VLBW) infants as early as the second week of life ( 162 ). Similarly, inhaled atropine has been shown to improve dynamic compliance in non-intubated patients with BPD ( 159 ).…”
Section: Medications Used In Bpdmentioning
confidence: 99%
“…Lungs of infants with BPD often have increased resistance and decreased compliance (157). The use of beta-agonists has been shown to reduce airway resistance in both intubated and non-intubated BPD patients and improve dynamic compliance and specific airway conductance in intubated BPD patients (158)(159)(160)(161). The use of salbutamol was shown to be effective in improving compliance and resistance in very low birth weight (VLBW) infants as early as the second week of life (162).…”
Section: Bronchodilatorsmentioning
confidence: 99%